Efficacy of eleven antimicrobials against a gregarine parasite (Apicomplexa: Protozoa) - Whitman Douglas W; Merisko Amber; Johny Shajahan (BMC, 2007)
Abstract Background The Apicomplexa are a diverse group of obligate protozoan parasites infesting a wide range of invertebrate and vertebrate hosts including humans. These parasites are notoriously difficult to control and many species continue to evolve resistance to commercial antibiotics. In this study, we sought to find an effective chemotherapeutic treatment against arthropod gregarines (Apicomplexa), and to identify candidate compounds for testing against other groups of protozoan parasites. Methods We tested eleven commercial antibiotics against a gregarine parasite of Romalea microptera grasshoppers. Infected insects were fed daily, lettuce containing known amounts of specific antibiotics. On Days 15 or 20, we measured the number of gregarines remaining in the digestive tract of each grasshopper. Results Treatment with metronidazole and griseofulvin in host insects significantly reduced gregarine counts, whereas, gregarine counts of insects fed, albendazole, ampicillin, chloramphenicol, fumagillin, quinine, streptomycin, sulfadimethoxine, thiabendazole or tetracycline, were not significantly different from the controls. However, albendazole produced a strong, but non-significant reduction in gregarine count, and streptomycin exhibited a non-significant antagonistic trend. Conclusion Our results confirm that gregarine infections are difficult to control and suggest the possibility that streptomycin might aggravate gregarine infection. In addition, the insect system described here, provides a simple, inexpensive, and effective method for screening antibiotics.